2011
DOI: 10.1111/j.1600-0501.2011.02210.x
|View full text |Cite
|
Sign up to set email alerts
|

Submerged and transmucosal healing yield the same clinical outcomes with two‐piece implants in the anterior maxilla and mandible: interim 1‐year results of a randomized, controlled clinical trial

Abstract: Transmucosal healing of two-piece implants is as successful as the submerged healing mode with respect to tissue integration and patient satisfaction within the first 12 months after IP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…As stated in the material and methods, the population of this investigation was partially the Madrid UCM arm of a multicentre investigation involving 11 centres (clinical trial registration (http://clinicaltrials.gov/ct2/show/NCT00906425) and 127 patients. The one‐year (Hammerle et al., ) and three‐year (Sanz et al., ) outcomes from this multicentre clinical trial have been previously published. At 1 year, the reported bone‐level changes were −0.47 and −0.48 mm, respectively, for the submerged and transmucosal groups and at 3 years (−0.68 and −0.58 mm, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in the material and methods, the population of this investigation was partially the Madrid UCM arm of a multicentre investigation involving 11 centres (clinical trial registration (http://clinicaltrials.gov/ct2/show/NCT00906425) and 127 patients. The one‐year (Hammerle et al., ) and three‐year (Sanz et al., ) outcomes from this multicentre clinical trial have been previously published. At 1 year, the reported bone‐level changes were −0.47 and −0.48 mm, respectively, for the submerged and transmucosal groups and at 3 years (−0.68 and −0.58 mm, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The patients from this investigation were partly a subset sample (the UCM arm) from the multicenter clinical trial, whose 1‐year and 3‐year results have already been published (Hammerle et al., ; Sanz et al., ). The initial sample belonging to the multicentre study consisted on 24 patients, which was enlarged to 40 patients (after obtaining the permission from the principal investigator and the sponsor of the multicentre clinical trial) and continued with the evaluation of these patients long term (5 years).…”
Section: Methodsmentioning
confidence: 99%
“…Just prior to loading, the submerged implants were surgically exposed. After 1 year of loading, the authors presented data on 126 implants that showed PD values of 2.5 and 2.4 mm and crestal bone loss of 0.47 ± 0.64 and 0.48 ± 0.65 mm for submerged and transmucosal implants, respectively [ 189 ]. Three years after placement, clinical data was available for 106 implants, showing mean crestal bone loss of 0.68 ± 0.98 mm (submerged healing) and 0.58 ± 0.77 mm (transmucosal healing) and similar PD values between 2 and 2.5 mm [ 190 ].…”
Section: Modsla: On Cp Ti Bone-level Implantsmentioning
confidence: 98%
“… In the majority of the studies evaluations were usually made by the researchers in a nonstandardized way (). Moreover, patient's opinions were scored using different methods, including visual analog scales, Likert scales, dichotomous or multiple choice answers and other scales.…”
Section: Subjective Assessment Of Esthetics: Patient‐reported Outcomementioning
confidence: 99%